CO2 absorption performance of PVDF/alumina hollow fiber membrane for membrane contactor application - Muhammad Syazwan, Shamsudin (2017)
In this study, fabrication of composite polyvinylidene fluoride (PVDF) hollow fiber membrane for carbon dioxide (CO2) absorption was successfully prepared via incorporating alumina clay as additive into polymer dope solution. 18 wt.% of PVDF hollow fiber membrane and 82wt. % of NMP was fabricated with various compositions of alumina clay (1 wt. %, 3 wt. % and 5 wt. %) via wet spinning process. The prepared membrane was characterized via contact angle and CO2 absorption performance was conducted at various monoethanolamine (MEA) concentrations and liquid flow rates. The hollow fiber membrane sample with 5% of alumina content (S4) showed the highest value around 92.4° when characterized via contact angle. The high value of the contact angle showed that the membrane has a high hydrophobicity which capable of reducing membrane wetting. The CO2 absorption at various flowrates and concentrations of MEA exhibited increasing trend of CO2 absorption flux upon addition of alumina clay concentration. The highest value of CO2 absorption flux recorded was 4.368 × 10−2 mol/m²s for the sample of PVDF/alumina with 5wt. % of alumina at 200 mL/min and 2M of MEA.